(untitled) (Communications in Computational Physics, 2008)
We present an extended update on the status of a particle-in-cell with Monte Carlo collisions (PIC-MCC) gun code developed at Los Alamos for the study of surface-converter H− ion sources. The program is fully kinetic. Some of the program's features include: solution of arbitrary electrostatic and magnetostatic fields in an axisymmetric (r,z) geometry to describe the self-consistent time evolution of a plasma; simulation of a multi-species (e−, H+, H2+ , H3+, H−) plasma discharge from a neutral hydrogen gas and filament-originated seed electrons; full 2-dimensional (r,z) 3-velocity (vr, vz, vφ) dynamics for all species; detailed collision physics between charged particles and neutrals and the ability to represent multiple smooth (not stair-stepped) electrodes of arbitrary shape and voltage whose surfaces may be secondary-particle emitters (H−and e−). The status of this development is discussed in terms of its physics content and current implementation details.